DON-DUKAKLI EKINLARNING ZARARKUNANDALARI VA ULARGA QARSHI KURASH CHORALARI - Sh.K. Babadjanova; L.Sh. Ruzimova; N.O.Cheshenbayeva (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
This article will analyze the main pests of cereals and legumes, their bioecological characteristics and the environmental impact they have on the agroecosystem. Pests cause significant damage to crop yields, reducing the sustainability of the agroecosystem. The article highlights their life cycle, reproduction rate, nutritional characteristics and adaptability to environmental conditions. The importance of environmental and sustainable pest control measures, including a biological and integrated protection system, is also emphasized.